Environmental regulations and firms' integration in global markets: using a new environmental performance index - Rafael Duarte Lisboa Paschoaleto; Inmaculada Martínez-Zarzoso (Empirica, 2024)
This paper investigates how the environmental performance of firms impacts their participation in global value chains (GVC). The analysis is based on a dataset of 15,922 firms located in 32 European, Central Asian, Middle Eastern, and North African countries, with information on firm-level environmental practices provided by the recent Green Economy module of the World Bank Enterprise Surveys. We propose the Firm Environmental Performance Index (FEPI), a new index measuring firms' adoption of environmental actions. The index is used in a two-part instrumental variable approach to estimate the impact of FEPI on both the probability and the intensity of GVC participation, while addressing reverse causality concerns. The results indicate that a one-standard deviation increase in the FEPI increases the probability of participation by 6.4 percentage points, a result consistently observed in all regions and sectors. The effects on the intensity of participation are mostly non-significant. However, a negative effect is observed in exceptional cases, namely for firms that are importers only, have low-technology practices, and are located in less developed regions. The results are robust to alternative definitions of GVC participation, inclusion of alternative instruments, and to partial violations of the exclusion restriction. All in all, they suggest that complying with environmental regulations could lead to higher integration in global markets, albeit with adverse effects in some particular cases.
Keywords: F10; 330; GVC; FEPI; Instrumental variables; World Bank green module; Firms; Environmental regulations